Health implications of radiological terrorism: Perspectives from Israel - Hagby Moti; Goldberg Avishay; Becker Steven; Schwartz Dagan; Bar-Dayan Yaron (Journal of Emergencies, Trauma and Shock, 2009)
September 11 th events taught us, members of the medical community, that we need to prepared for the worst. Nuclear terror is no longer science fiction. Radiological weapons of mass terror come in three flavors: The first one is nuclear. Since 1992, there have been six known cases of highly enriched uranium or plutonium being intercepted by authorities as it passed in or out of the former Soviet Union. Constructing a nuclear fission weapon requires high-level expertise, substantial facilities, and lots of money. All three of which would be difficult, although not impossible, for a terrorist group to pull off without state support. However, terrorists could carry out potential mass destruction without sophisticated weaponry by targeting nuclear facilities using conventional bombs or hijacked aircrafts. Terror attacks could also carry out mass panic and radioactive contamination of people and environment by dispersal of radioactive materials with or without the use of conventional explosive devices. Most medical and para-medical personnel are not familiar with CBRN terror and radiation casualties. To lessen the impact of those potential attacks and provide care for the greatest number of potential survivors, the community as a whole - and the medical community in particular - must acquire the knowledge of the various signs and symptoms of exposure to irradiation and radioactive contamination as well as have a planned response once such an attack has occurred. Based on knowledge of radiation hazards, medical emergency planers should analyze the risks of each scenario, offer feasible solutions and translate them into internationally accepted plans that would be simple to carry out once such an attack took place. The planned response should be questioned and tested by drills. Those drills should check the triage, evacuation routes, decontamination posts, evacuation centers and receiving hospitals. It is crucial that the drill will consist of simulated casualties that will follow the evacuation route from point zero to the ED. Knowledge and exercise will reduce terror (fear) from radiation and help the community as a whole better cope with such an event. This article will review the general information of radiation types, their biological damage, clinical appearance and general concepts of nuclear event planning, focusing on medical response and focus on the Israeli perspective.